]Hubungan Brand Awareness Dan Kualitas Pelayanan Produk Dengan Keputusan Pembelian Di Store Matahari (Survei Pada Mahasiswa Fakultas Ekonomi Universitas Slamet Riyadi Surakarta) - Purnomo, Valerius Setyo; Nurcahyani, Eva; A, Bilqis Fairuzzain; R, Rosita Dwi; Rahadhini, MD (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of brand awareness and service quality on consumer purchasing decisions at Matahari Department Store, especially at the Singosaren Surakarta outlet. The background of this study is based on the increasing competition from e-commerce and the shift in consumer behavior towards online shopping, which requires conventional retailers to better understand the factors that determine purchasing decisions. The method used is a quantitative approach with a purposive sampling technique for 50 respondents. The data collection instrument used a five-point Likert-sized closed questionnaire, and its validity and reliability were tested using statistical methods. Data analysis was carried out through the Spearman Rank correlation test and multiple correlation analysis. The results showed that brand awareness has a significant and strong relationship with purchasing decisions, with a correlation coefficient value of 0.784. Likewise, service quality has been shown to have a significant effect on consumer purchasing decisions. These findings indicate the importance of companies to continue to improve brand image and service quality in order to maintain loyalty and increase consumer purchasing intensity amidst increasingly competitive market dynamics.